Analysis of Pedestrian Movement on Delhi Roads by Using Naturalistic Observation Techniques. Issue 1 (2017) - Jha, Abhaya; Tiwari, Geetam; Mohan, Dinesh; Mukherjee, Sudipto; Banerjee, Subhashish
Pedestrian fatalities constitute about 30% of the deaths caused by road traffic crashes in India. The proportion of pedestrian fatalities in large cities (Delhi, Mumbai, etc.) varies from 50% to 60% and is about 20% to 30% on national and state highways. Pedestrians are present on all road categories in urban as well as rural areas. At least 20% to 40% of work trips are taken as pedestrian trips in most Indian cities. However, on pedestrian facilities such as footpaths, safe crossing facilities are not present in most Indian cities. Even when present, their poor maintenance and poor construction quality make them unusable. As a result, pedestrians are forced to share the road space with motorized vehicles and to cross the roads where there is no safe pedestrian crossing. This paper attempts to study pedestrian behavior—walking along the road and crossing the road—by detecting pedestrians with the use of a vehicle-mounted camera. The vehicle is driven on various categories of roads at different times. The data collected with this method are varied temporally as well as spatially. A smartphone–based GPS logging app was used to collect telemetry data, which were synced with the camera feed. The objective of this study was to understand pedestrian behavior—walking on the road versus a footpath in the presence of various road features, such as the number of lanes, presence of medians, and presence of footpaths. The influence of the presence of public transport stops, junctions, foot bridges, and grade-separated junctions (flyover) on pedestrian crossing behavior was studied.